Constructing entrepreneurial orientation in a selling context: the qualitative attitude approach - PELTOLA, Soili; VESALA, Kari Mikko (Economics and Business Review, 2025)
This paper explores the construction of attitudes in argumentative talk to underscore the context-specific nature of the dimensions of entrepreneurial orientation (EO) and their interrelations. The material comprises interviews in which the directors, who form the management group of a Finnish firm, individually commented on a statement that ‘each salesperson is an autonomous entrepreneur’. Our analysis identified two opposing evaluations of entrepreneurial autonomy, which were labeled as proactive selling and internal competitive aggressiveness. The analysis points out limitations on the realistic and positivist premises of the conventional EO measures by identifying related yet differing understandings which actors involved in everyday organizational practices display in their talk.